Adropin Levels in the Serum of Obese Type 2 Diabetic Patients and their Relationship to Oxidative Stress - Layla A. Mustaf (African Journal of Advanced Pure and Applied Sciences, 2023)
Background: Adropin, a peptide hormone translated from energy Homeostasis and insulin sensitivity. This study aims to investigate serum adropin level of type2diabetes mellitus (T2DM) patients, especially in obese patients, finding the relationship between oxidative stress and adropin levels. This study consisted of 30 patients with 30 healthy people; their ages ranged from (30-65) year of both sexes (12) females and (18) males for each patients and healthy peoples. The patients with T2DM showed significantly lower serum adropin levels and glutathione (GSH) concentration than those in healthy people. At the same time, glucose, malondialdehyde (MDA), peroxynitrite, and total lipids were higher concentrations in patients with T2DM than healthy people. It was concluded that the levels of adropin are inversely proportional to the concentration of glucose in the blood and positively correlated with GSH, MDA, peroxynitrite, total lipids, and body mass index.